Dinamika Meaning Making Process pada Emerging Adults dengan Riwayat Adverse Childhood Experiences dan Non-Suicidal Self-Injury - Herdianto, Adeline; Dewi, Zahrasari Lukita (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2022)
Non-Suicidal Self-Injury (NSSI) is a maladaptive phenomenon that becomes a concern in Indonesia, especially in the prevalence of emerging adults. One of the predisposing factors for NSSI is exposure to Adverse Childhood Experience (ACE). Individuals in these two contexts are also found to have different worldviews. The aim of this study was to describe the dynamics of meaning-making in the context of emerging adults with a history of ACE and NSSI. This study uses a qualitative-phenomenological approach. Interviews were conducted with three participants aged 19-25 years, having 5-8 ACE (ACE questionnaire screening), doing NSSI (NSSI-AT screening), and live in Jabodetabek. Participants were selected by purposive sampling. Thematic analysis of the data was carried out according to the theory of meaning-making model, ACE, and NSSI. The results showed that distress by adversive experience triggered the meaning-making process. The role of the deliberate and cognitive process is more helpful in the dynamics of meaning-making. The meanings made, such as acceptance, re-appraisal, re-attribution, perceptions of growth, and changes in global meaning, were found to reduce distress and generate compassion. However, the meanings made can still be dynamically developed throughout the individual's life. In further research, exploration in the gender role, culture, and other humanistic aspects, such as forgiveness and support system in meaning-making can be carried out. Longitudinal or mixed-method methods can also be chosen to develop the results of this study.